Deoxygenation Trends and Their Multivariate Association with Self-Reported Fatigue in Post-COVID Syndrome - Anja-Maria Ladek; Marianna Lucio; Andreas Weiß; Thomas Knauer; Helena Sarmiento; Miriam Ilgner; Marie Jakobi; Laura Barteczko; Marion Ganslmayer; Jürgen Rech; Antonio Bergua; Christian Y. Mardin; et al. (Biomedicines)
Background/Objectives: A relevant subgroup of post-COVID-19 syndrome (PCS) patients suffers from post-exertional malaise (PEM) and cardiovascular or neurological symptoms, impairing daily functioning up to becoming even house- or bedbound. Recent data suggest that PCS summarizes different subgroups, one of them being characterized by an impaired microcirculation. Thus, the aim of the present study was to investigate local deoxygenation, measured with non-invasive near-infrared regional spectroscopy (NIRS), and its association with self-reported fatigue in patients with PCS compared to controls in light exercise. Methods: 150 participants (100 PCS patients and 50 controls) were recruited. PEM was assessed using FACIT, Chalder, and Bell scoring and Canadian Criteria. NIRS was used to measure local oxygenation while kneading a stress ball and during recovery. Results: PCS patients showed fatigue scores of 30 (Bell score), 20.6 (FACIT fatigue score), and 9.914 (Chalder fatigue score). Decreased deoxygenation peaks at the start of exercise were observed in patients with PCS, compared to controls (p = 0.0002). Multivariate analysis identified a subgroup, showing an association between strong fatigue and restricted oxygenation dynamics. Conclusions: NIRS could be a potential tool to assess deoxygenation deficits even in moderate to severely impaired PCS patients using light exercise protocols.